(untitled) - ELBYTRA, BERDHAN (Language Horizon: Journal of Language Studies, 2014)
CONVERSATIONAL ANALYSIS OF LANGUAGE USED BY GENDERS IN WILL SMITH’S ‘HITCH’ MOVIE Berdhan Elbytra S-1 English Literature, Languages and Arts Faculty, Surabaya State University, berdhanelbytra@gmail.com Abstrak Pada dasarnya, bahasa digunakan untuk berkomunikasi dengan orang lain. Selama orang lain memahami makna dan memberikan tanggapan, percakapan sudah dimulai, tetapi banyak orang tidak tahu bagaimana untuk membuka dan menutup percakapan terutama ketika mereka mendekati lawan jenis dengan tujuan untuk memikat mereka. Beberapa mengatakan bahwa mereka takut ditolak dan beberapa mengatakan bahwa mereka tidak yakin bahwa mereka mampu melakukannya bahkan itu hanya berbasa-basi. Fakta ini berlaku untuk setiap manusia di seluruh dunia. Banyak orang berhasil dan banyak orang tidak. Film HITCH memberikan beberapa contoh kegagalan dan kesuksesan dalam mendekati wanita. Penulis disini melihat dari pemahaman bahasa untuk mendekati lawan jenis. Oleh karena itu penulis mengklasifikasikan perbedaan karakter bahasa. Interaksi sosial adalah cara primordial melalui mana usaha dari dunia sosial ditransaksikan, identitas peserta ditegaskan atau ditolak, dan budaya yang ditransmisikan, diperbaharui dan dimodifikasi. (Goodwin dan Heritage, 1990: 283) Dengan meningkatnya gerakan feminis dalam masyarakat Barat pada tahun 60-an dan 70-an dari abad kedua puluh, kenaikan dalam sosiolinguistik dan psikolinguistik seputar hubungan antara bahasa dan jender muncul. Banyak kemajuan berharga dari karya linguistik yang diterbitkan dari para ahli bahasa mengenai ide-ide yang berbeda tentang topik ini. Pembahasan mengenai Gender dan Bahasa ini bermula setelah adanya publikasi buku dari Robin Lakoff “Language and Women’s Place”, dan Deborah Tannen “Gender and Discoure”. Banyak terima kasih terutang kepada Lakoff dan Tannen, yang berhasil menarik perhatian pengamat dalam linguistik, dan telah memimpin kemajuan penelitian di bidang ini menyangkut bahasa dan gender. Karya ilmiah ini mencoba membahas perbedaan bahasa antara laki-laki dan perempuan dalam percakapan di film HITCH, dan percakapan dianalisis dengan teori-teori dalam penelitian ini, misalnya: Karakter Bahasa> Gaya Bahasa> Agresivitas Verbal, Gangguan, dan Pergantian Topik. Hasil analisis data menunjukkan perbedaan karakter Bahasa antara pria dan wanita dalam film HITCH.Penulis mencoba memberikan analisis yang jelas tentang perbedaan percakapan antara laki-laki dan perempuan. Disamping itu, penulis berharap dapat memberikan beberapa pencerahan kepada pembaca tentang perbedaan bahasa disetiap gender demi meningkatkan kompetensi komunikatif mereka dalam berbahasa. Kata Kunci: AnalisisPercakapan (CA), Bahasa dan Gender, Gender danJenisKelamin, Film, Hitch. Abstract Basically, the language used to communicate with others. As far as others understand the meaning and give a response, the conversation is already begun; but many people do not know how to open and close a conversation especially when they are approaching opposite sex in order to attract them. Some says that they are afraid of being rejected and some says that they are not sure that they are able to do it even it is just a small talk. This fact applies to every human all around the world. Many people made it and many people do not. The HITCH movie gives some of these examples of the failure and the successful approach to women. The writer here sees from the language understanding in order to approach opposite gender. Therefore the writer classifies the language character differentiation. Social interaction is the primordial means through which the business of the social world is transacted, the identities of its participants are affirmed or denied, and its cultures are transmitted, renewed and modified. (Goodwin and Heritage, 1990: 283) With the rising of feminist movements in Western societies in the 60’s and 70’s of the twentieth century, an upsurge in sociolinguistics and psycholinguistics surrounding the relation between language and gender appeared. Many valuable linguistic works were published and linguists advanced different ideas on this topic. It is especially so after the publication of Robin Lakoff’s Language and Women’s Place and Deborah Tannen's Gender and Discourse. Many thanks are owed to Lakoff and Tannen, who successfully draws scholars’ attention in linguistic circle, and has led the progress of research in this field concerning language and gender. This study focuses only on the conversations in HITCH movie and the conversations are analyzed by the theories in the study, for example: Language Character > Language Style > Verbal Aggressiveness, Interruption, and Topic Shift. The result of the data analysis reveals the Language character differentiation between men and women in HITCH movie. The author tries to give a clear analysis about the differences between men’s and women’s language. Meanwhile, the author hopes to give some enlightenment to the readers about language and gender differentiation to improve their communicative competence. Keywords: Conversational Analysis (CA), Language and Gender, Gender and Sex, Movie / Film, Hitch. INTRODUCTION Differences in the ways that men and women use language have long been interesting to be studied. A significant reason is the lack of agreement over the best way to analyze language. In this research, gender differences in language use were examined using standardized categories to analyze a movie called HITCH. Women used more words related to psychological and social processes. Men referred more to object properties and impersonal topics. Although these effects were largely consistent across different contexts, the pattern of variation suggests that gender differences are larger on tasks that place fewer constraints on language use. Looking at the phenomena of men approaching woman are already familiar to us. They are always trying to attract women so that they have a life companion, who sometimes looks like a little pushy. As stated in ‘Male Sex Drive’ (Hollway 1984) or ‘Men Can’t Help Their Sexually Aggressive Behavior’. Masculinity and femininity, as well as individual women and men, and indeed gender relations, can be represented in particular ways in discourse in a whole range of written and spoken texts (Mills 1995). Even sadder, by their power, they sometimes approach a woman just because they want to clear their head, you know, get in, get off, get out, and tell to the other man the tricks, how to, or tutorial of how to get women easily, yes, that is what they say easy. Quarrel, too, often took place between the opposite genders; it all depends on the language used by each gender. Most of the quarrel happens because men do not understand women, more than the vice-versa. These happened because women never tell what is in their mind literally. Men and women are very different, body and soul, so the way they dress and the language used are different too. Since then appeared misunderstanding between them. Language has been used to communicate, and transfer their mind, so understanding the language becomes the most important thing to get to know each other well. By understanding the language differentiation between men and women, this study hopefully helps the reader to understand each other more than ever. So the misunderstanding between men and women can be reduced. Speak is a social activity. As with other social activities, language activities can be achieved if people are involved in it. In the talk, the speaker and the listener are equally aware that there are rules governing the conduct, use of language, and interpretations of the actions and sayings of his interlocutor. Each participant is responsible for the acts of said action and deviations from the rules of language in social interaction (Alan in Wijana, 2004: 28).Inside there is also a language of communication ethics, and the ethics of communication in itself there is moral. Have the same sense of moral decency containing the doctrine of good and bad deeds. Thus, the act is judged as good or bad deeds (Burhanuddin, 2001:102). Ethics can also be defined as the science of behavior or talk about human behavior, which is considered good and what is evil. Meanwhile, in a simple (Poedjowijatna, 1986: 23) said that specific targets of ethics to human actions are deliberate. Thus, it can be concluded that the realization of linguistic awareness from men to women are not contains a lot of ethics. Suparno (1988: 3) explains in his article, that the diversity of languages ??is not polite to be a common thing to say especially between men. The Sarcasm actually makes intimacy without bulkhead strata, so that those who use the language variety can be enjoyed by happy and proud to be. Language is a means communication in daily life. As its functions language brings people into relationship with their environment. Language is, therefore, socially learned behavior, a skill that is acquired as we grow up in society (Boey, 1975: 3). According to Holmes (1992: 2), “People usually use language to ask for and to express their feeling of indignation, annoyance, happiness, sadness, admiration, respect, and etc.” People can also share information, experiences or stories, state the idea, opinion, and also deliver the message to others. Language has an important role in the process of social interaction. Language is not only used in oral communication but also it is used for communicate such as writing. Language can be delivered trough movement, code, and symbols. Language is not simply a means of communicating information. It can be concluded that a language is used as a means of communication and as medium for expressing feeling. Communication according to Crystal (2008: 89) it refers to the transmission and reception of information (a ‘message’) between a source and a receiver using a signaling system. The signaling system are speaking system, writing system, or signaling system (body language, hand signal). Either what system used, the most crucial thing in a communication is whether other people understand the meaning or not. Conversation is one of the most prevalent uses of human language. All human beings engage in conversational interaction and human society depends on conversation in order to function: “Social interaction is the primordial means through which the business of the social world is transacted, the identities of its participants are affirmed or denied, and its cultures are transmitted, renewed and modified.” (Goodwin and Heritage, 1990: 283) In this modern era, there are many ways people act to entertain others. One of the entertainments available is movie. It makes some producers, authors, or directors, are working together to attract the viewers through the best quality of their movie. In order to attract the viewers, they create interesting theme which makes good movie, and the casts consist of famous and talented actors who appear in front of the camera, and follow the script. All of those criteria will support the film to deliver the idea of the movie. Film is social script that catches the soul of an era zeitgeist of the society. The audience will feel close to the theme that appears, even as the audience looks themselves. Language is a sign system characterized by arbitrary signs, discrete elements and constraining grammar. “Film signs contain of language, on the other hand, are motivated cannot be neatly separated out, and their combinations only the rather particular rules of certain traditions” (Hill and Gibson, 1988: 5). Based on previous researchers, the study about gender and language differentiation is always interesting to be discussed because many students did this kind of research. It is because many researchers want to support for their own developing or established view and to take claims made by linguists in the past (such as Robin Lakoff’s list of differences between men and women’s language use) and apply these two language data from the present – we can no longer verify Lakoff’s claim in relation to men and women in the USA in 1975, but we can see if they are true now of men and women in our own country or locality. Language and gender involves interpreting the use of linguistic resources to accomplish social ends, (Eckert & McConnell-Ginet, 2005: 79). Language differentiation often start quarrel between men and women, to understanding gender and language and character differentiation between men and women can be seen from language style, language use, and topic. Based on the background of the study, the statements of the problems are: Whatarethelanguagecharacterdifferentiationbetweenmenandwomen in HITCHmovie? SeenfromLanguage Style, andLanguage use Howarelanguagedifferentiationbetweenmenandwomen in HITCH movie? Seen from: Topic and Pattern of Speech With the all the data collection, the questions, and answer, the result of this study is significant for some reasons as follows: It is hoped that this study is usefultoenrichourinsightinlinguisticsin orderto understandwhat the language differentiation between men and women are. Moreoverthis studymayhelpthereadersknowhowtousethetheoriestowardsthesituation of placewherethespeechoccurs in order to make a good conversation. The study examines the language differentiation between men and women in HITCH movie. The study intends to apply the Conversational Analysis (CA) as the main theory and the second theory is Gender and Language understanding in analyzing the conversation between men and women. The figure below is a sequence procedure of data analysis taken from Miles &Huberman which drawn into three structures as follows: Data Collection Data Reduction Data Display Conclusion: Drawing / Verification Figure 1.1: Components of data analysis: Interactive model taken from Miles &Huberman (1994: 12) METHOD This study is a descriptive qualitative research because the data is in the form of utterances uttered by the character in the movie. Most of the data were collected by conducting a non–participant observation. In the non–participant observation the researcher is not involved in any situation in the movie making process. He turn on the DVD on, listen, transcribe, and analyzing the conversation in the Hitch movie based on the theory of Deborah Tannen. According to Bogdan and Taylor in Moeleong (2000: 3) Qualitative research is a research procedure that represents the descriptive data such as words in written and oral from the people and the behavior that can be observed. According to Creswell (2012: 214) a non-participant observation is an observation in which the observer visits a site and records notes without becoming involved in the activities of the participants. The subject of the study is the movie called HITCH. This movie tells about New York’s date doctor, Alex Hitchens. Firstly, Alex Hitchens being the professional date doctor, the ways of him teaching good people to act positively towards women in order to attract them is confirmed to be nearly perfect. There is no doubt that his methods works well. He had been teaching the methods for so many times and he is confirmed by his clients to be the best date doctor in New York because all of them has successfully reach their targets, in this situation is women. Secondly, not like any other romantic movie that played by one or two main characters, this movie played by four main characters (Alex, Sara, Albert, and Allegra) with the different point of view. It means that on the other hand, Alex was a tall handsome man and professional, yet Albert was neither handsome nor professional, and both try to generate a relationship with women that are beautiful. By all means, in this movie there are several conversations between men and women that can be analyzed. This was the main reason why this movie was chosen as the research subject in this study. This study has been conducted in the movie HITCH. The character in the movie that the observer chooses to be observed are using the English language and the main conversation occurs is about how to attract women. Since English had been used in many country, the observer choose the characters that are natives from the United States of America because the English from this country have been institutionalised easier to be heard and learned than anywhere else, and this standard variety, until very recently, have its English are used as reference models for the teaching of English throughout the world (Cheshire, 1991: 3) The source of the data is only from the conversations in HITCH movie. The observer then conduct a research from the dialogues between four main characters in the movie. The data was acheived with comparing the study by Deborah Tannen, and the observer classifies it according to its types. In order to clarified the data, the observer would mention the examples of conversation of how to attract women, and the second is some conversations that has been mentioned is analized and compared to Deborah Tannen's studies. The data is acquired through citation. The technique is need in this study is descriptive qualitative research. Data analysis is a method of analyzing written, verbal or visual communication messages (Cole in (Elo&Kyngas, 2007:1–pdf)). Since the data is from the HITCH movie script, it answers these two kinds of questions: 1) What are the language character differentiations between men and women in HITCH movie? Seen from: a) Language Style and b) Language use. 2) How are language differentiations between men and women in HITCH movie? That seen from: a) Topic and b) Pattern of Speech. The procedure consist of three current flows activities: data reduction, data display and conclusion drawing/verification. Nevertheless, before going through three below flows the data firstly was processed. The data obtained were processed by transcribing the result of HITCH movie conversations. The source of the data is only in HITCH movie’s conversation transcript that was being analized in form of written language by using the theory of Language and Gender by Deborah Tannen. In transcribing the data, the researcher used the conversation with several modifications and adaptation. Here are some codes and explanations that are no longer being explained in the future: Code Explanation / // [...] “...” Bold ( B ) Italic( I ) AH AB AC SM CH MD KC NL TR VM Pauses Interruptions/overlap For comments Previousconversation Word(s) tobefocused on Sippet/quotation Alex Hitchens Albert Brennaman AllegraCole Sara Melas Chip Mandy Casey Neil Tom Reda VanceMunson Table 1.1: Codes and explanations RESULT AND DISCUSSION Men and women were created to live in pairs, but what often happens is quarrel between them due to differences in the character. Men have harsher character than women; it means that men more often disturb and dominate women. But there are men who really do not know how to approach women, so that the ways they used are wrong although for them it was true. Differences in the character of the language also affect the style of language speech. Men are known more often than women cursing because people judge that if the woman does not deserve to curse because when women curse, they are considered less feminine. As discussed in chapter 1 that men grew following his father's behavior and women followed her mother's behavior, then if all is turned upside down so that all considered improper or inappropriate. Since then women sometimes feel uncomfortable when talking with a man who often cursing and men are also uncomfortable when talking to talkative or tacky women. In this section will be discussed further on the language character differentiation. By understanding the differences in language character, this study expected relationships between men and women can be better understanding each other. So every time the conversation between men and women, they are able to understand the character of his interlocutor. And more than that, they can adjust their personal character with their interlocutor. Language character differentiation can be seen from the language style which consists of: a) topic shift, b) verbal aggressiveness, and c) interruption). From language use, it consist of three characters, they are: a) Hedges, b) Tag Question, and c) Empty Adjective. The next following extracts are taken from the HITCH movie script. Language Character Differentiation 2. 3. 4. 5. 5.1 1.1. Language Style When a speaker takes a turn in conversation, she or he can begin by explicitly acknowledging the contribution of the previous speaker and can then talk on a topic directly connected with what was gone before. It seems that this is a pattern typically adopted by women. Men on the other hand do not feel they have to make a link with the previous speaker’s contribution; on the contrary, men are likely to ignore what was been said before and to concentrate on making their own point. As mentioned before, language style can be seen from topic shift, verbal aggressiveness, and interruption, thus the following extracts shows it all. 1.2. Topic Shift As stated in the previous theory, the topics shift tend to be sudden in the conversation of all-men, while women usually build each other’s contributions, so that the topic goes progressively developed in conversations and topics shift occurs gradually. Here lies the difference between men and women. Men changed the subject to discuss another topic, but women although the shift the topic, they are staying focused on one topic. 1.3. Verbal Aggressiveness As stated in chapter two, interruptions is talk by another speaker during current speaker’s turn. In society, women seem more gentle in speech than men, and therefore men are automatically becomes the figure that often interfere women. Men are proven to interrupt women more than the vice versa, with the result that women are less able to complete their turns at talk and tend to talk less. As a result, men tend to dominate topics of conversation and women tend to take on the role of listener. In other words, women are less aggressive than men. Tannen states that an interruption has little to do with beginning to make verbal sounds while someone else is speaking, which she calls Overlap. It has to do with dominance, control, and showing a lack of interest or support. When a person does not offer support to a fellow conversant but makes an effort to wrench control of the topic of conversation, Tannen calls it Uncooperative Overlap. "Overlapping is a way to keep conversation going without risking silence" (Tannen, 1990: 205). TS-1/LC/LS/I Men Women I couldn'thelpbutnoticeyoulook a lot likemynextgirlfriend You'rewelcome. So do youlikeCubanfood? Youhavefantasticeyes. Areyoualwayssoshut-downandafraid you should try mine, it's great Table 1.2: Overlap interruptions comparison between men and women (Coates, 1986: 98-99). 1.4. Interruption Men’s interruptions, on the other hand, seem to have their goal the seizing of a turn and therefore they are perceived as an attempt to deny the current speaker’s right to complete a turn. Mixed conversations between men and women as stated in Coates. J, (1986: 97, 98, 99) Men’s use interruptions results in women not talking. From the conversations above it can be seen that men are more inclined than women to change the subject, and the topic shift that uttered by Chip is interrupting Sara, which brings to the theory of Interruption. As stated in chapter two above, interruptions is talk by another speaker during current speaker’s turn. In society, women seem more gentle in speech than men, and therefore men are automatically becomes the figure that often interfere women, let's look at the following conversation to prove that women frequently interpolate remarks, offer enthusiastic comments, as well as nodding and making minimal responses during another speaker’s turn. In the context of all-women interaction, such behavior is not seen as an attempt to deny the current speaker the rights to complete her turn, but as evidence of active listenership. Language Use 2.1. Hedges A hedge is a mitigating word or sound used to lessen the impact of an utterance. It could be regarded as a form of euphemism. Hedges may intentionally or unintentionally be employed in both spoken and written language since they are crucially important in communication. Hedges help speakers and writers indicate more precisely how maxims (expectations of quantity, quality, manner, and relevance) are observed in assessments. Like what Lakoff said that women use hedges more often than men, it can be seen from the following conversation between the two women. Sarah spoke to her colleagues in the office of the news in the paper. In a brief conversation, there are some hedges in it. SM : They came together, they danced together, Ana they left together. W : He's cute, in a sheepdog kind of way. SM : For all I know, he's adorable. But him canting her is... W : You seem stressed. SM : You and I had an understanding. If you invite Allegra, you're supposed to call me. W : Sara, I didn't invite her. Honestly, sweetie, I thought she was still in Europe. In conversation, it can be observed that information conveyed by the speaker is limited by adding “all I know”, “I thought”, and “you seem”. By so saying, the speaker wants to inform that she is not only making an assertion but observing the maxim of quantity as well. If the speaker only says that “she is still in Europe” and she do not know for sure if she (Allegra) is in Europe, she may violate the maxim of quality since she say something that she do not know to be true or false. Nevertheless, by adding “I thought”, the speaker wants to confirm that they are observing the conversational maxim of quality. By using “you seem”, what has been said by the speaker is not relevant to the moment in which the conversation takes place. For men, they usually do not use hedges because they usually are always confident in what he says, although it is not 100% correct. 2.2. Tag Question As stated in previous study, a tag question is a grammatical structure in which a declarative statement or an imperative is turned into a question by adding an interrogative fragment – the "tag"-- (Geoff Parkes, 1989: 38). In most languages, tag questions are more common in colloquial spoken usage than in formal written usage. They can be an indicator of politeness, emphasis or irony. They may suggest confidence or lack of confidence; they may be confrontational, defensive or tentative. Although they have the grammatical form of a question, they may differ from questions in that they do not expect an answer. For example: AH: Justbreathe. How'ditgo? [Fallingpattern] AB: I yelledather. I screamedatmyboss! I quitmyjob! AH: What? [Risingpattern] AB: Yousaid, / I gottagoback. AH: No, I didn'ttellyoutoquit. Relax.Okay? [Risingpattern] listen, we'refine. AB: Wouldyouletmego? [Risingpattern] AH: Albert, no! Justrelax! Okay? [Risingpattern] Justletitmarinate for a second. Trust me. The word "Okay?" repeated several times by Alex, it was not to receive an answer, but to ask Albert to calm down. So although they have the grammatical form of a question like “What?” and “Okay?” they may differ from questions in that they do not expect an answer. Sometimes such questions are answered by the listener because the listener does not understand that this type of tag question does not need to be answered, but to be done. 2.3. Empty Adjective Empty adjectives work the same was as normal adjectives because they describe a noun i.e. big, small, fast etc. Empty adjectives, however, are so called because they are hard to define. Where adjectives such as “big” are easy to define (because it can mean something of great stature and excessive in size) empty adjectives are difficult to give a concrete definition to and are not particular to a subject. Examples of empty adjectives include “lovely”, “good”, “Amazing”, and “fantastic”, etc. Empty adjectives are applied to soften and add friendly elements to the sentence, although they are did not add any particularly meaningful content. For example: “In the dark knight” instead of “In the night”. Night is dark, so the word “dark can be removed because it is un-necessary. But women use this to soften the language that they use. Instead of “He is such a big fat liar” consider “He is a liar". Lakoff (1975) claims that if a man uses these terms he appears more feminine as it damages his masculine prestige e.g. ‘divine, lovely, adorable, delightful and sweetie’. In a conversation between women and men often are empty adjective that we do not realize. Use of empty adjective is intended to make a sentence to be more beautiful to listen to. In the following conversation, there are a few empty adjectives: AC: Thiswas a fantasticidea. AB: Isuppose. Hey, where'sMaggie? AC:Late as usual. Instead of “fantastic”, it can be change into “good”, and “I suppose” can be change into “thank you”. Empty adjectives can be change into another word or even can be removed. For example: 59) AH: So, wait / thatstuffworked for you? AC: Itwasadorable. Whatdidyou do? AH: Nothing. / Absolutelynothing. The word “adorable” and “stuff” canberemovedwithoutcausinganymeaningchangesinthesentence. CLOSING CONCLUSSION Based on the results and discussion, which presented in previous chapter, it can be concluded that women and men are both have different characters that leads to have different language. This movie shows all the characteristics and language of men and women. The conversation focuses on how to attract women by understanding their characteristic, although in such case there are some bad example of how to attract women. All in all, the movie gives the right ways of how to attract women to some men who really like women, not who just want to sleep with them. It also provides the right ways to do towards the situation by showing the characteristic of women as follows: Women tend to give another speaker chances to another speaker to finish their talk and women are more focus on the topic without changing the topic until it is finished. Men, on the contrary, they tend to overlapping another speaker and changing the topic which considered as interruption. Men are more aggressive in talking so the way they talk are more harsh, men often curse just for a common conversation, it is makes women uncomfortable because they are soft spoken and rarely curse unless in certain situation that makes them upset. Topic of talking of women are so different than men, women talks about their relationship to other women, and rather than talking about the feeling, men talking about how to get into a relationship; Men talks about business, women talks about men. By talking to the same gender with the interesting topic, the conversation continues for a long time although – in this case, men – the topic always change. But on the other hand when both women and men are talking a different topic, the conversation lasts quicker, this because the topic maybe consider as not interesting or not important to one of the genders. Style of language that used by men, are mostly harsh and yet, women are softer, this is because the decision of each gender to follow who. It means that when a boy becoming a man, they are – sure – decided to choose to be his father, and when a girl tries to be her mother, they put the make-up on, they dressed like princess (to be a complete women) because he choose to grow to be her mother. As for a girl are not allowed to talk harshly, let alone swearing, they are forcing themselves to be more polite to the public (in this case to the strangers, not to the close person) Sentence use of men and women are also different, although the way they are talking are quiet similar, but the smallest piece such as hedges and tag question, are differing from both genders. Like when women, you know, they are using tag questions more often than men, not because they are not sure all the time, but because they just want to be polite. This leads back to the gender they are choose, and if for example, men talking with tag questions often, they are considered as sissy or gay. Differentphrasesdiscrepancycategoryapproximatesthecategoryof politeforms (e.g., “Wouldyoumindif … ,” “Should I getthedoor?”). Fittingwithearlierwork, the researcher found a smallbutreliabletendency for suchwordstoappearmoreofteninwomen’stexts (e.g., Holmes, 1995; McMillanetal., 1977).has twocategoriesrelevanttothecriticallinguistic area of hedging, buttheseyieldedsurprisinglydifferentresults. Newhedgingcategory, combining“I” with a variety of verbssuch as “guess,” foundtheexpected gender difference:Women weremorelikelytohedge (cf. Hartman, 1976; Mulac&Lundell, 1994;Poole, 1979). However, womenwerenomorelikelytousewordsfromthetentativecategory (e.g., maybe, perhaps). The use of phrases, such as “I guess,” mayreflectpreviousfindingsthatwomenusemorepoliteforms (Holmes, 1995;McMillanetal., 1977), andarereluctanttoforcetheirviews on otherpeople.Backtoourtopicagain, thereisstill a lot tobedoneinthefield of gender differencesandlanguage. Gender differenceis a fundamental partand a basicfact of human life. Soitisnosurprisingtofindthespecificdifferencesreflectedinlanguage. Sociolinguistsaretryingtoworkout a list of gender pattern. The gender patterninvolvesthedifferentuse of certainlinguisticformsbydifferentgenders, theirdifferentstyles, etc. Itishopedthatthiswillleadto a betterunderstanding of thedifferentuses of women’sspeechandmen’sspeech, of thelinguisticrelationshipwiththegenders, andtosmoothdomesticand International communicationbetweendifferentgenders. SUGGESTIONS As the language of men and women are different, the topic of the conversation is important. If men talks about personal feeling or women talks about car engine, it is odd to be heard because the gender are not what we have, but it is what we do. So each sex should choose the topic that suits for their gender, not the other way around unless in a certain situation. Next, for the interruption, is important o let another speakers turn to talk and staying on the topic until it is done before changing another topic. Language used by each gender is different too, so choose the perfect words that occur in the certain place and time. Each gender should learn the language use by the opposite gender in order to avoid the quarrel or any of unwanted situations. For the readers, further study of gender and language, it needs to find sources of any kind, whether movie, books, online media, or direct conversation will help the findings to the study. Therefore the hard finding of the theories and data can be reduced. ACKNOWLEDGEMENT Foremost, PraisebetoJesusChristtheAlmighty for givingmeblessing of health, strength, ability, andbrilliancethat I finallycanaccomplishthisthesisentitled“Conversational Analysis Of Language Used By Genders In Will Smith’s ‘HITCH’ Movie” andI wouldliketoexpressmysinceregratitudetomysupervisors: Drs. SlametSetiawan, M.A., Ph. D. as my advisor for his concern in set the title of my thesis and as thehead of EnglishDepartment of State University of Surabaya and also as mysubstitute of my former very first advisor, Suharsono, M. Phil., Ph. D. LisetyoAriyanti, SS., M.Pd. and Adam Damanhuri, SS., M.Hum. as mythesisadvisorexaminers for theconcernsandsupportstoguidemeinfinishingmythesis revision. Yuri Lolita, S.Pd., ST, M.Pd. as myacademic supervisor duringmystudyatEnglishDepartment. Drs. Fahri, MA, as a person who considerate and suggests me to change the thesis supervisor and also give me chance to enroll for thesis trial. Drs.Much. Khoiri, M.Si. As the first person who suggest my very first thesis title and contents. Forallimportantencouragementandinputscontributedtothisthesis. MygratefulnessisalsogiventoEnglishDepartmentlecturerswhohavesharedimmenseknowledgeduringmystudy. Moreover, I alsothankadministrativestaffsandlibrarians of Faculty of Literature. I thankthefriends, family, andstrangerswhoofferedmetheirtalk, lettingme tape andanalyzethem. Some of thosewhohavebeenhelpfulinotherwaysare: My family: Bambang RiinSuasonoYudho,EdalyGethruida, You YoulaniTjipto, Anggraeny Tjipto, Betlehem Efrata, Lucy Lampshade, Greg Abbot, Maharani, BremyAnugerah. My Friend: Bagus AndriasWidianto, Dara Langgeng Cholis, ErlinAprilia Efendi,Eva Damayanti, HaryoParikesit, Henny Eka Ristiana, Mona, Echa, Soni Prasetyo Arifin, DickyIndraRusmana, RinaldyRochim, TangkasPriambodo, Sapriyadi, Daniel Akbar. Online Friend: Jacko Kruger, Lisa, Pearlyn Xuan, Michelle Phan. I beganto work on thisprojectsincethesecond semester of mycollege(2009) withthesupportfrommyfriendsandcompletedwithsupportfrommygirlfriendandhermother. I remaindeeplygrateful for theseinvaluableperiods of uninterruptedresearchtime. I owespecialthankstomyunusuallydedicatedandableprojectobservers, Anggraeny Tjipto andYouYoulani. A significantpart of thewritingwasstartedwhile I wasfinallyfoundthebook "TalkingVoices, by: Deborah Tannen" broughtbymylecturerLisetyoAriyanti, SS., M. Pd. when I wasfollowingthediscourseanalysisclass. And the writing was done whenDrs. SlametSetiawan, M.A., Ph. D.lend me the Gender and Discourse by Deborah Tannen. Finally, I shouldappreciatetocontributivepeoplethatcan not bementionedonebyone. REFERENCES Zimmerman, D. and West, C. 1975. Sex Roles Interruptions and Silences in Conversation In Thorne, B. and Henley, N. (eds) Language and Sex: Difference and Dominance. Massachusettes: Newbury House. Trudgill, P. 1974. Sociolinguistics: An Introduction to Language and Society. Harmondsworth: Penguin Books Ltd. Hutchby, I. and Wooffitt, R. 2008. Conversational Analysis. Polity Press: Cambridge University Press Coates, J.1986. Women, men and language: A sociolinguistic account of sex differences in language. London & New York: University of Lancaster Tannen, D. 1994. Gender and Discourse. New York: Oxford University Yule, G.1998.The Study of Language. Third Edition: Cambridge University Brend, R. 1975. Male-female Intonation Patterns in American English In Thorne andHenley. Language and Sex: DifferenceandDominance. Mass:Newbury House Brown, P. 1987. Politeness: Some Universals in Language Usage. New York: Cambridge University Press. Coates, J. 1986. Women, Men and Language: A Sociolinguistic Account of Sex Differences in Language. New York: Longman Inc. Fishman, P. 1980. Conversational Insecurity. Language: Social Psychological Perspectives. Oxford: Pergamon Press Freeman, R. and McElhinny, B. 1996. Language and Gender. In McKay, SL. & Hornberger,NH. (eds.)Sociolinguisticsand Language Teaching. Cambridge: Cambridge University Press. Gomme, I. 1981. A Study of the inferior image of the female use of the English language as compared to that of the male. UK: Edge Hill College. Gumperz, J. J. 1971. Language in Social Groups. Stanford: Stanford University Press. Jespersen, Otto. 1922. Language:Its Nature, Development and Origin. London: Allen and Unwin Lakoff, R. 1975. Language and Woman’s Place. New York: Harper & Row. Macaulay, R. K. S. 1977. Language, Social Class and Education. Edinburgh: Edinburgh University Press. Macaulay, R. K. S. 1978. Variation and consistency in Glaswegian English. In Trudgill, P. (ed.)Sociolinguistics Patterns in British English. London: Edward Arnold. McConnell-Ginet, S. & Borker, R. & Furman, N. (eds.) 1980. Women and Language in Literature and Society. New York: Praeger Publisher. Smith, P. M. 1985. Language, the Sexes and Society. Oxford: Basil Blackwell. Stockwell, Peter. 2002. Sociolinguistics: A Resource Book for Students. London: Routledge